In vitro conservation of gametes: the way forward to conserve the genetic resources of autochthonous sheep breeds - Mujitaba, Malam Abulbashar; Kútvölgyi, Gabriella; Egerszegi, István; Vass, Nóra; Bodó, Szilárd (Animal welfare, Ethology and Housing Systems (AWETH), 2023)
Assisted reproductive technologies (ARTs) significantly improved livestock productivity and reproductive performance and enabled elite parents to produce thousands of offspring globally. However, indiscriminate use ARTs, lack of information and materials on autochthonous sheep breeds (ASB) resulted in a loss of their genetic resources (GnR), thus shooting up the number of at-risk and extinct ASB globally. This problem is more in Europe and the Caucasus region, Africa, and Asia, according to the FAO 2005, 2017, and Sustainable Development Goals, 2022 reports. Considering the current economic challenges, in vivo gene conservation (INGC) is expensive and less sustainable. Therefore, an in vitro gene conservation (IVGC) can supplement the INGC for better efficiency and sustainability. The current review explored the pros and cons of ARTs on ASB’s GnR, the need to conserve their GnR through IVGC, and the prospects of the IVGC on ASB’s GnR conservation. Interestingly, Vitrification with reduced volume (e.g., cryotop) is the leading technique in oocyte cryopreservation, as it results in lower cryoprotectants toxicity, better oocyte viability, and pregnancy rates aside from being cheap and field-friendly than the other vitrification techniques. With oocyte and spermatozoa cryopreservation from the same breed, an extinct breed of interest can be regenerated in a single generation. However, oocyte cryopreservation holds a considerable prospect in IVGC, but the technique in sheep still needs improvements.
Keywords: sheep; cryopreservation; oocytes; control slow rate freezing; vitrification; assisted reproductive technologies